A contemporary theology of the cross viewed in relation to Filipino religiosity. - Wangawang, Noemi B. (Singapore : Southeast Asia Graduate School of Theology, 1983)
The purpose of this study is to critically seek to understand Filipino religiosity and the significance of the cross of Christ with such religiosity. Though the emphasis of this study is theological, the long centuries of colonization, specifically during the Spanish era as a historical background of this study, cannot be dispensed with, in trying to understand Filipino religiosity with that of a contemporary theology of the cross. In this study, that phase of Philippine history could not be ignored if we are to be better understand the problem and its solution.
In partial fulfillment of the requirement for the degree Master of Theology
A thesis submitted to the faculty, Southeast Asia Graduate School of Theology
Thesis (M.Theo.) -South East Asia Graduate School of Theology